Patient-initiated electronic health record amendment requests. (26th May 2014) - Hanauer, David A; Preib, Rebecca; Zheng, Kai; Choi, Sung W
Abstract: Background and objective Providing patients access to their medical records offers many potential benefits including identification and correction of errors. The process by which patients ask for changes to be made to their records is called an 'amendment request'. Little is known about the nature of such amendment requests and whether they result in modifications to the chart. Methods We conducted a qualitative content analysis of all patient-initiated amendment requests that our institution received over a 7-year period. Recurring themes were identified along three analytic dimensions: (1) clinical/documentation area, (2) patient motivation for making the request, and (3) outcome of the request. Results The dataset consisted of 818 distinct requests submitted by 181 patients. The majority of these requests (n=636, 77.8%) were made to rectify incorrect information and 49.7% of all requests were ultimately approved. In 6.6% of the requests, patients wanted valid information removed from their record, 27.8% of which were approved. Among all of the patients requesting a copy of their chart, only a very small percentage (approximately 0.2%) submitted an amendment request. Conclusions The low number of amendment requests may be due to inadequate awareness by patients about how to make changes to their records. To make this approach effective, it will be important to inform patients of their right to view and amend records and about the process for doing so. Increasing patient access to medical records could encourage patient participation in improving the accuracy of medical records; however, caution should be used.